Use of Serotonin Norepinephrine Reuptake Inhibitors in the Treatment of Attention-Deficit Hyperactivity Disorder in Pediatrics. (January 2014) - Park, Pauline; Caballero, Joshua; Omidian, Hossein
Objective: To review the current literature on the efficacy and safety of serotonin norepinephrine reuptake inhibitors in the treatment of attention-deficit hyperactivity disorder (ADHD) in the pediatric population.Data Sources: A literature search from 1996 to August 2013 was conducted using MEDLINE, CINAHL, and EMBASE databases. Search terms included attention-deficit hyperactivity disorder, serotonin norepinephrine reuptake inhibitor, pediatric attention-deficit hyperactivity disorder, venlafaxine, duloxetine, desvenlafaxine, milnacipran, and nefazodone .Study Selection and Data Extraction: Relevant articles on duloxetine and venlafaxine for the treatment of pediatric ADHD were reviewed; 5 studies on venlafaxine and 1 study on duloxetine were evaluated. Studies included open-label and randomized, double-blind trials. Case studies in pediatric populations and all studies in adult populations were excluded.Data Synthesis: Patients 6 to 17 years old were evaluated in the venlafaxine and duloxetine studies. Trials on venlafaxine, ranging from 2 to 6 weeks, showed patient improvement as measured by the Conners Rating Scale and ADHD Rating Scale. Venlafaxine was initiated at 12.5 to 25 mg/d and titrated up to 1.4 to 3.8 mg/kg/d to a maximum of 150 mg/d. Duloxetine showed minimal efficacy in treating ADHD symptoms at doses of 60 mg/d at 6 weeks. The most common side effects for venlafaxine and duloxetine included drowsiness and decreased appetite, respectively.Conclusions: Data for venlafaxine and duloxetine are limited. However, venlafaxine may be considered as an alternative agent when patients cannot tolerate or fail stimulants, tricyclic antidepressants, or bupropion. Duloxetine has been studied in children; however, with only 1 study available, it is difficult to recommend.